Inferential reading, a key to enhance reading comprehension - Ochoa Montaña, Judy; Ochoa Montaña, Judy; Mesa Cárdenas, Sandra Liliana; Pedraza Orduz, Yaqueline; Orlando Caro, Edgar (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article arises from the reflection on the results obtained in reading competence, by the students of 3rd and 5th grades of the Educational Institution “Sugamuxi”, in the Saber 2015 tests, the information of the Synthetic Index of Educational Quality and the contributions of some theorists such as Sole, Mendoza and Pérez. The results obtained in the diagnostic phase developed with the Educational Action Research methodology will be reported. First, it presents an analysis of the problems in relation to reading; Afterwards, it makes a background review about the subject, it continues with a referential frame that guides the proposal; and presents the diagnosis of the existing problem in terms of reading levels. It ends with a reflection on the educational task and the importance of strengthening pedagogical practices to improve reading comprehension.